2019
DOI: 10.4314/rjmhs.v2i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Indwelling urinary catheter use and associated outcomes among adult patients undergoing surgery

Abstract: Background: Indwelling Urinary catheters (IUCs) are the most utilized devices. They are complicated into postoperative catheter-associated urinary tract infections, urethral trauma, pain that culminate into prolonged immobility and hospital stay with associated financial implications. The aim of this review was to give an overview of the use of indwelling catheters among adult patients undergoing surgery. Methods: A systematic review approach was employed. A literature search was done using of search engines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Mobility challenges related to the IDUC, including prolonged time to ambulation (walking without the support of a nurse), immobility and discomfort, overlap with previous findings. 36 In this study, patients reported feeling dependent on nurses’ directives which could have delayed the moment of mobilisation and thereby have a negative influence on the discharge date. 37 38 …”
Section: Discussionmentioning
confidence: 72%
“…Mobility challenges related to the IDUC, including prolonged time to ambulation (walking without the support of a nurse), immobility and discomfort, overlap with previous findings. 36 In this study, patients reported feeling dependent on nurses’ directives which could have delayed the moment of mobilisation and thereby have a negative influence on the discharge date. 37 38 …”
Section: Discussionmentioning
confidence: 72%